X-ray reverberation lags from the 1.5 Seyfert galaxy NGC 5273. Issue 1 (17th December 2019) - Vincentelli, F M; Mastroserio, G; McHardy, I; Ingram, A; Pahari, M
ABSTRACT: We present the results of X-ray spectral-timing analysis of a 90 ks XMM–Newton observation of the nearby, broad-line, early-type AGN NGC5273. The X-ray spectrum revealed the clear presence of a reflection component at high energies, with a clear signature of a narrow iron line at 6.4 keV, consistent with distant reflection. Applying a relativistic reflection model, we found only marginal evidence for a broader relativistic line component. However, cross-spectral analysis revealed that, between 4 and 6 × 10 −4 Hz, the 5–8 keV band lagged the 2–3 keV band, implying reflection of the iron line from material close to the black hole. From the analysis of the lag-energy spectrum, we found a broad, but skewed line with a peak of ≈1000 s at 7.5 keV relative to the continuum, which we interpret as the iron line in the reverberation spectrum from an illuminated accretion disc. From the asymmetry in the shape of lag-energy spectrum, we also found that the source is consistent with having an inclination ≥45°.